PERBANDINGAN KARAKTERISTIK MINYAK KAYU PUTIH DARI VARIETAS TANAMAN YANG BERBEDA - Woesono, Hastanto Bowo; Nofriansyah, Wahyu (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2019)
This study aims to determine the effect of varieties and duration of leaf storage on yield and quality of cajuput oil. The study used a completely randomized design with factorial experiments. The first factor is the variety of eucalyptus plants and the second factor is the duration of leaf storage. The parameters observed in the study included yield, specific gravity, refractive index, optical rotation, cineol content, oil color and solubility in alcohol. The results showed that the variety and duration of leaf storage had a very significant effect only on the yield yield parameters, with a value of 0, 7%, while the quality of cajuput oil such as cineol content, specific gravity, refractive index, does not have a real effect, but for optical rotation has a real effect. The results of the study show the quality standard on the color parameters and cineol content of cajuput oil have not been included in the range of the Indonesian National Standard, but the values of specific gravity, refractive index, optical rotation and solubility in alcohol have met the Indonesian National Standard. Keywords: plant varieties, storage time, oil quality